ChemInform Abstract: Crystal Structure and Magnetic Properties of the S = 1/2 Quantum Spin System Cu7(TeO3)6F2 with Mixed Dimensionality. Issue 39 (23rd September 2014) - Hu, Shichao; Mace, Amber; Johnsson, Mats; Gnezdilov, Vladimir; Lemmens, Peter; Tapp, Joshua; Moeller, Angela
Abstract Single crystals of the title compound are grown hydrothermally from an aq.